For Whom the Bell Tolls: Silver Alerts Raise Concerns Regarding Individual Rights and Governmental Interests - Wasser, Tobias D.; Fox, Patrick K. (Journal of the American Academy of Psychiatry and the Law Online, 2013)
The Silver Alert system was initially created to help protect missing persons who have cognitive impairments, particularly the elderly. The Silver Alert is modeled after the Amber Alert, created to help locate and safeguard missing children. Unlike the Amber Alert, however, in most states the Silver Alert applies to the elderly, adults with a mental impairment, or both, depending on the state. The goal of the Silver Alert system is the quick dissemination of information about missing persons to law enforcement personnel as well as to the general public. Previously, states notified law enforcement personnel of missing persons through teletype to other public safety jurisdictions to enlist their assistance in the retrieval of the missing person. Silver Alert programs substantially expand the notification to include the general public, who receive information through radio and television broadcasts as well as highway billboards. The programs serve a legitimate governmental interest by protecting a vulnerable population from possible harm. Yet, the implementation of these alerts can have unintended consequences, including the possible violation of an individual's right to privacy. Such consequences require careful consideration.